Early Childhood Education and Life-cycle Health - Jorge Luis García; James J. Heckman (Institute of Labor Economics (IZA), 2020)
This paper forecasts the life-cycle treatment effects on health of a high-quality early childhood program. Our predictions combine microsimulation using non-experimental data with experimental data from a midlife long-term follow-up. The follow-up incorporated a full epidemiological exam. The program mainly benefits males and significantly reduces the prevalence of heart disease, stroke, cancer, and mortality across the life-cycle. For men, we estimate an average reduction of 3.8 disability-adjusted years (DALYs). The reduction in DALYs is relatively small for women. The gain in quality-adjusted life years (QALYs) is almost enough to offset all of the costs associated with program implementation for males and half of program costs for women.
Keywords: I10; J13; I28; C93; 330; early childhood education; life-cycle health; long-term forecasts; program evaluation; randomized trials